PENGARUH METODE PROJECT BASED LEARNING DALAM PEMBELAJARAN MENULIS TEKS EKSPOSISI - Sholih, Muhamad Miftah; Aeni, Eli Syarifah (IKIP Siliwangi, 2019)
From the results of observations made by the author, one of the problems with the current Indonesian language material is that students have difficulty when recording exposition text skills due to a lack of student interest in learning as well as an understanding of the material being studied and a lack of student understanding. Therefore, this problem gets the author's special attention to conduct research with innovative learning methods. The formulation of the problem of this study is knowing the effect of the Project Based Learning method on recording exposition text? The purpose of this study is to determine the effect of the Project Based Learning method on the skills to record exposition texts, increase student creativity, and practice critical thinking. The research method used was quasi experiment with the type of nonequivalent control group design supported by descriptive qualitative. The pretest stage of pretest scores got the highest points of 70 medium 65, and the lowest points 55. After the treatment was given showed an increase in the students' Posttest score the highest score was 90, the medium value was 85, and the lowest score was 75. From the scores obtained the material noted that the text of the exposition felt more effective. That way, students can determine the structure of the exposition text and be able to overcome the problems found to be rich in understanding gained by emphasizing training themselves through complex activities, conducive classroom structuring, and the creative role of the teacher making the learning process better and feel efficient.